거골 골연골 병변의 분류와 치료의 최신 지견 - 한희수; 이경민; Hee Soo Han; Kyoung Min Lee (대한족부족관절학회지, 2025)
An osteochondral lesion of the talus (OLT) is a frequent cause of chronic ankle pain in young, active individuals because of cartilage and subchondral bone damage with limited healing capacity. This review outlines updated classification systems incorporating the etiology, lesion morphology, and associated factors like instability or malalignment, offering tailored treatment pathways. Although small, stable lesions may respond to conservative treatment or bone marrow stimulations, the long-term outcomes are often limited because of fibrocartilage degeneration. For larger or unstable lesions, arthroscopic osteochondral autograft transfer and chondrocyte implantation could provide more durable cartilage restoration, with recent advances minimizing surgical morbidity. Adjuncts may enhance healing, including bone marrow aspirate concentrate and other adjuvants used in autologous matrix-induced chondrogenesis. Arthroscopic techniques allow access to previously difficult lesions, enabling comprehensive, minimally invasive management. The optimal outcomes depend on matching the treatment to the lesion type and correcting the coexisting pathologies. Although further long-term studies are needed, recent developments have improved the clinical approach to OLT.